2018
DOI: 10.1111/bjh.15085
|View full text |Cite
|
Sign up to set email alerts
|

PDCD1 and CTLA4 polymorphisms affect the susceptibility to, and clinical features of, chronic immune thrombocytopenia

Abstract: Programmed death-1 (PD-1, PDCD1) and cytotoxic T lymphocyte-associated antigen-4 (CTLA-4, CTLA4) play central roles in immune checkpoint pathways. Single nucleotide polymorphisms (SNPs) of PDCD1 and CTLA4 have been reported to be associated with susceptibility to some autoimmune diseases. However, the potential association between SNPs in these immune checkpoint genes and risk of chronic immune thrombocytopenia (cITP) remain controversial and obscure. The aims of this study were to clarify the influence of PDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 30 publications
(34 reference statements)
2
10
0
Order By: Relevance
“…These results are consistent with the Li's study, which indicated that the rs3087243 is not associated with susceptibility to ITP in a Chinese population [14]. However, in a Japanese population study, the rs3087243 was found to be significantly associated with susceptibility to chronic ITP [22]. The controversial results obtained may be due to the different ethnic population studied.…”
Section: Discussionsupporting
confidence: 88%
“…These results are consistent with the Li's study, which indicated that the rs3087243 is not associated with susceptibility to ITP in a Chinese population [14]. However, in a Japanese population study, the rs3087243 was found to be significantly associated with susceptibility to chronic ITP [22]. The controversial results obtained may be due to the different ethnic population studied.…”
Section: Discussionsupporting
confidence: 88%
“…With better epidemiological data, it became clear, that this variant is present in the Caucasian population with a frequency of close to 50%. The CT60/G polymorphism was reported in Grave's disease, AIHA, and chronic ITP; yet, CT60/G had a weak link to T1D in other studies . Thus, the association between the polymorphisms in CTLA4 and the susceptibility to autoimmune diseases remains controversial …”
Section: Ctla‐4 and Other Diseasesmentioning
confidence: 97%
“…Overall, length of ICI therapy, advanced disease, or extensive prior therapy did not appear to correlate with the severity of the thrombocytopenia, which is consistent with the current literature. [29][30][31] As with traditional ITP, ir-TCP is a diagnosis of exclusion. In all the cases, there was a clear temporal relationship between ICI administration and the onset of thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%